Mutual optical intensity propagation through non‐ideal mirrors. (18th August 2017) - Meng, Xiangyu; Shi, Xianbo; Wang, Yong; Reininger, Ruben; Assoufid, Lahsen; Tai, Renzhong
Abstract : A simulation method based on the mutual optical intensity model is developed for simulating the propagation of partially coherent radiation through non‐ideal mirrors. Abstract : The mutual optical intensity (MOI) model is extended to include the propagation of partially coherent radiation through non‐ideal mirrors. The propagation of the MOI from the incident to the exit plane of the mirror is realised by local ray tracing. The effects of figure errors can be expressed as phase shifts obtained by either the phase projection approach or the direct path length method. Using the MOI model, the effects of figure errors are studied for diffraction‐limited cases using elliptical cylinder mirrors. Figure errors with low spatial frequencies can vary the intensity distribution, redistribute the local coherence function and distort the wavefront, but have no effect on the global degree of coherence. The MOI model is benchmarked against HYBRID and the multi‐electron Synchrotron Radiation Workshop ( SRW ) code. The results show that the MOI model gives accurate results under different coherence conditions of the beam. Other than intensity profiles, the MOI model can also provide the wavefront and the local coherence function at any location along the beamline. The capability of tuning the trade‐off between accuracy and efficiency makes the MOI model an ideal tool for beamline design and optimization.